2015
DOI: 10.3340/jkns.2015.58.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Ruptured Pericallosal Artery Aneurysms

Abstract: ObjectiveAneurysms arising from the pericallosal artery (PA) are uncommon and challenging to treat. The aim of this study was to report our experiences of the endovascular treatment of ruptured PA aneurysms.MethodsFrom September 2003 to December 2013, 30 ruptured PA aneurysms in 30 patients were treated at our institution via an endovascular approach. Procedural data, clinical and angiographic results were retrospectively reviewed.ResultsRegarding immediate angiographic control, complete occlusion was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…2,9 There are many known factors which affect the outcome of DACA aneurysms after surgical intervention, but there is sparsity of publication on these issues. 1,2,4,9,16,25 High H&H and MF grades, ICH, IVH, hydrocephalus, IOR, timing of surgery, and advanced age have been attributed for poor outcome after intervention. 1,9,10,25 Furtado et al found poor clinical grade on admission and initial ICH as a risk factor for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,9 There are many known factors which affect the outcome of DACA aneurysms after surgical intervention, but there is sparsity of publication on these issues. 1,2,4,9,16,25 High H&H and MF grades, ICH, IVH, hydrocephalus, IOR, timing of surgery, and advanced age have been attributed for poor outcome after intervention. 1,9,10,25 Furtado et al found poor clinical grade on admission and initial ICH as a risk factor for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 4 7 14 These days endovascular technique, which has been flourishing day by day, is equally effective for the treatment of ruptured DACA aneurysm. 12 13 14 16 17 18 22 Truly speaking, DACA aneurysms are difficult to treat either by surgery or endovascular procedures due to their fragility, small-sized dome, wide neck, broad-based origin, and peripheral location. Many recent studies have shown similar results of both procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 A summary of nine studies on endovascular treated ruptured PAAs reported a favorable outcome (mRS ≤ 2) in 164/219 (74.9%, range 53% - 100%) cases. 11 …”
Section: Discussionmentioning
confidence: 99%